Spontaneous Symmetry Breaking in the Formation of Supramolecular Polymers: Implications for the Origin of Biological Homochirality. (2nd January 2019) - Karunakaran, Suneesh C.; Cafferty, Brian J.; Weigert‐Muñoz, Angela; Schuster, Gary B.; Hud, Nicholas V.
Abstract: Aqueous solutions of the achiral, monomeric, nucleobase mimics (2, 4, 6‐triaminopyrimidine, TAP, and a cyanuric acid derivative, CyCo6) spontaneously assemble into macroscopic homochiral domains of supramolecular polymers. These assemblies exhibit a high degree of chiral amplification. Addition of a small quantity of one handedness of a chiral derivative of CyCo6 generates exclusively homochiral structures. This system exhibits the highest reported degree of chiral amplification for dynamic helical polymers or supramolecular helices. Significantly, homochiral polymers comprised of hexameric rosettes with structural features that resemble nucleic acids are formed from mixtures of cyanuric acid (Cy) and ribonucleotides (l‐, d ‐pTARC) that arise spontaneously from the reaction of TAP with the sugars. These findings support the hypothesis that nucleic acid homochirality was a result of symmetry breaking at the supramolecular polymer level.